Memoria histórica, lugar de memoria y comunidad discursiva: materiales para el abordaje de un caso de archivo - Vitale, María Alejandra; Minardi, Adriana Elizabeth (Diálogos Latinoamericanos, 2013)
In this artícle we aim to discuss some notions about the construction process on historical memory in order to focus in a particular example of lieux de mémoire. In the first place, we analize critical concepts like lieux de mémoire, historical memory and the political uses of Memory, according to the hegemonic construction. Then, we pay attention to a crucial concept to understand the meaning of archive: lieux de mémoire. We organize the article by considering Pierre Nora´s theory, looking forward to discuss the archives generation process in a material, symbolic and functional sense. We expose these ideas by demonstrating a methodology to analize memory archives, by taking as an example the DIPBA file (Buenos Aires Province Police Direction of Intelligence Archive). Some relevant conclussions close the article.